INTERACTION OF STATE AND CIVIL SOCIETY IN RUSSIAN ANTI-CORRUPTION SYSTEM - Albov, Alexey; Ivanets, Galina; Kupriyanova, Lyudmila; Petrusevich, Tatiana; Shatskaya, Irina (Revista Inclusiones, 2020)
The problems in the steady social progress are caused by inadequate legal and organisational levels of anti-corruption efforts, specifically in the social sphere. Achievements in countering grassroots corruption ultimately affect the living standards and financial and moral wellbeing of people. Accordingly, this paper concentrates on developing the forms and methods of interaction of the state and civil society in countering corruption in the social sphere. The aim is to demonstrate the potential of interaction between the state and civil society in the anti-corruption system and to eliminate the causes and conditions determining the level of corruption in the social sphere using the tools of administrative law.